STUDENTS' TEST ANXIETY AND ITS CORRELATION WITH THEIR ACADEMIC PERFORMANCE : A Study of Undergraduate Students at a Private Higher Education Institution in Bandung - Fitria, Nur Ainani (2013)
At the university levels, test anxiety does exist. Considering that many language testing researchers, specifically test anxiety researchers, agree with the phenomena that the effect of test anxiety on test performance can infiltrate other aspects and cannot be underestimated, therefore, it is necessary to investigate the students' test anxiety. Besides, in Indonesia, there are only a small number of studies which have taken the subject of test anxiety.This study was intended to examine the general situation of EFL students' test anxiety, especially among undergraduate students at a private higher education institution in Bandung. The units of analysis explored in this study included the test anxiety levels experienced by EFL students, factors that have caused EFL students' test anxiety, and correlation between students' test anxiety and their academic performance.The data were collected by using a battery of self report measures (i.e. Spielberger's Test Anxiety Inventory (TAI) 1980 and Test Anxiety Inventory retrieved and adapted from Academic Centers for Excellence) and a semi-structured interview. To see the correlation between the students' test anxiety and their academic performance, a correlation analyses was used. For an accurate computation, SPSS (Statistical Package for Social Sciences) was applied. The research showed that the students experienced low, moderate, and high test anxiety levels. The majority of the students (52.69%) experienced low anxiety. Factors affecting their test anxiety in terms of test taker characteristics included self-image, other people's view, preparation, future security, testing situation factors, the willingness to get a high score, personal problems, and situational and subjective determinants of test anxiety. Meanwhile, in terms of test characteristics, factors affecting their test anxiety included item type, time pressure, length of the test, item difficulty sequencing, and test taking information. Finally, the findings showed that the students' test anxiety had no significant correlation with their academic performance. Nevertheless, whether or not their test anxiety had statistically significant correlation with their academic performance, reducing the discomfort that some highly anxious test takers experienced would seem to be a laudable undertaking in an academic setting. Key Words: test anxiety, academic performance, correlation between students' test anxiety and their academic performance